Anti-inflammatory Prophylaxis Prevents Heterotopic Ossification in Contralateral Side Hip Arthroscopy: A Case Report - Warschawski, Yaniv (J Orthop Case Rep, 2017)
INTRODUCTION: Heterotopic ossification (HO) after hip surgery is the formation of bone in non-skeletal tissue, usually between the muscle and the joint capsule. HO after hip surgery may be associated with clinical sequelae such as pain, impingement and decreased range of motion, compromising surgical outcomes. CASE REPORT: A 20-year-old basketball player presented with a 2-year duration of the left groin pain after a basketball-related injury. Due to continued disability and failure of conservative management the patient underwent hip arthroscopy. No HO prophylaxis was given. Follow-up radiographs at 3 months after left hip arthroscopy showed Grade 3 HO on the left side. On the 2(nd) post-operative visit, the patient complained of contralateral (right-sided) hip pain. Due to continued symptoms on the right side and failure to respond to conservative management the patient underwent right hip arthroscopy. HO prophylaxis was initiated with non-steroidal anti-inflammatory medications (NSAIDs) treatment (Etodolac) 600 mg/day for 14 days. Follow-up radiographs at 3 months after the right hip arthroscopy showed no HO. CONCLUSION: This case demonstrates the efficacy of HO prophylaxis in a single patient. Routine HO prophylaxis with NSAIDs should be considered for patients undergoing hip arthroscopy with osteoplasty. A minimum of 9 weeks post-operative follow-up is recommended to assess the radiographic presence of HO.